Androgen biosynthesis during minipuberty favors the backdoor pathway over the classic pathway: Insights into enzyme activities and steroid fluxes in healthy infants during the first year of life from the urinary steroid metabolome. Issue 165 (January 2017) - Dhayat, Nasser A.; Dick, Bernhard; Frey, Brigitte M.; d'Uscio, Claudia H.; Vogt, Bruno; Flück, Christa E.
Graphical abstract: Highlights: Male androgen biosynthesis shows a significant peak at week 7 during minipuberty. Androgens in minipuberty are (at least in part) produced through the backdoor pathway. Steroid enzyme activities in the first year of life are all age-, some sex-specific. Steroid enzyme ratios obtained from urine GC–MS are comparable between laboratories. Abstract: The steroid profile changes dramatically from prenatal to postnatal life. Recently, a novel backdoor pathway for androgen biosynthesis has been discovered. However, its role remains elusive. Therefore, we investigated androgen production from birth to one year of life with a focus on minipuberty and on production of androgens through the backdoor pathway. Additionally, we assessed the development of the specific steroid enzyme activities in early life. To do so, we collected urine specimens from diapers in 43 healthy newborns (22 females) at 13 time points from birth to one year of age in an ambulatory setting, and performed in house GC–MS steroid profiling for 67 steroid metabolites. Data were analyzed for androgen production through the classic and backdoor pathway and calculations of diagnostic ratios for steroid enzyme activities were performed. Analysis revealed that during minipuberty androgen production is much higher in boys than in girls (e.g. androsterone (An)), originates largely from the testis (An boys -An girls ), and uses predominantly the alternative backdoor pathway (An/Et; Δ5 < Δ4 lyase activity). Modelling of steroid enzyme activities showed age-related effects for 21-, 11-, 17-hydroxylase and P450 oxidoreductase activities as well as 3β-hydroxysteroid dehydrogenase, 11β-hydroxylase type 1/2 and 5α-reductase activities. Sex-related characteristics were found for 21-hydroxylase and 5α-reductase activities. Overall, our study shows that androgen biosynthesis during minipuberty favors the backdoor pathway over the classic pathway. Calculations of specific diagnostic ratios for enzyme activities seem to allow the diagnosis of specific steroid disorders from the urinary steroid metabolome.